The Effect of Quizizz-Based Learning Media on Students' Learning Outcomes in Informatics Subject for Grade X Students At SMK Negeri 7 Bengkulu City - Selvera Amanda; Asnawati Asnawati; Hermawansa Hermawansa (Jurnal Komputer Indonesia, 2026)
This study aims to determine the effect of Quizizz-based learning media on students’ learning outcomes in the Informatics subject for Grade X students at SMK Negeri 7 Kota Bengkulu. This research used a quantitative method with a one group pretest-posttest design. The sample consisted of 49 students, including 23 students from Class X PH 3 and 26 students from Class X PH 4. Both classes were treated as one research group to examine the difference in students’ learning outcomes before and after the use of Quizizz. The data were collected through a pretest and posttest, with the Minimum Mastery Criterion (MMC) set at 75. The results showed that the students’ pretest scores ranged from 55 to 66, while the posttest scores ranged from 78 to 88. The average pretest score was 60.78, which increased to 82.80 in the posttest, resulting in an average improvement of 22.02 points. Learning mastery also improved, as none of the students achieved the MMC before using Quizizz, while all students successfully reached the MMC after learning through Quizizz. The hypothesis test using the Paired Sample t-Test obtained a mean difference of 22.020, a standard deviation of 0.520, a standard error mean of 0.074, a t-count value of 296.424, and df = 48. At a significance level of 0.05 with a two-tailed test, the t-table value was 2.01063. Therefore, t-count 296.424 > t-table 2.01063, and the significance value was 0.000 < 0.05, meaning that H₀ was rejected and Hₐ was accepted. Based on these results, it can be concluded that Quizizz-based learning media has a significant effect on improving students’ learning outcomes in the Informatics subject for Grade X students at SMK Negeri 7 Kota Bengkulu.